Development Of Co-Sr Carbonated Hydroxyapatite For Biomedical Applications - Noor, Muhammad Syazwan Mohd (Universiti Sains Malaysia, 2017)
Cobalt-strontium Carbonated Hydroxyapatite (Co-Sr CHA) was synthesized via nanoemulsion method. Cobalt (Co) and Strontium (Sr) ions were introduced into the apatite structure in order to improve their mechanical properties and enhance the biological activity which closely mimics to the bone mineral. CHA powders were used as a reference for Co-Sr CHA powders as a comparison in this study. The suitable synthesis temperature to produce nano-size powders in this study was at room temperature (RT). Four different compositions of Co-Sr CHA powders were synthesized using same technique. Among the as-synthesized powders, Co-Sr CHA 1 and Co-Sr CHA 2 were chosen as optimum composition and used for fabrication of dense products. Sintering was then performed on the dense samples of Co-Sr CHA at sintering temperature 900˚C and it cooled down with a dry CO2 atmosphere at temperature 200˚C. All the sintered samples of Co-Sr CHA were found to retain as B-type CHA. The use of dry CO2 atmosphere was found can compensate the carbonate loss during sintering at high temperature. The relative density and diametral tensile strength (DTS) values obtained for Co-Sr CHA 1 were 89.15% and 7.67 MPa respectively and it showed that Co-Sr CHA 1 has better mechanical properties if compared to sintered samples of CHA and Co-Sr CHA 2. For bioactivity test, the formation of apatite layer occurred on the surface of sintered samples of multi-doped CHA after soaking in SBF solution for 7 days. Co-Sr CHA 1 showed good bioactivity by the fastest formation of apatite layer if compared to other sintered samples. The amount of cobalt and strontium in the apatite structure were influenced the mechanical and bioactivity of the products. Thus, substitutions of cobalt and strontium in the structure successfully enhanced the properties of CHA-based material.